SOME BACTERIA ISOLATED FROM MARINE PLANKTON AND MUD - GORE, P S (Fishery Technology, 2025)
Fiftyseven bacterial strains isolated from marine plankton and mud from the inshore waters of Cochin are described. The flora of the plankton was dominated by chromogens while mud sample& failed to produce chromogens. The different strains are divided into five arbitrary groups for the convenience of description. The flora is similar to that of Mandapam (east ccast) while it differed from the flora of Calicut (west coast) in tlic paucity of Baci!TusÂ· sp and other sporeformers.